2014
DOI: 10.1111/iere.12070
|View full text |Cite
|
Sign up to set email alerts
|

For-Profit Search Platforms

Abstract: We consider optimal pricing by a profit-maximizing platform running a dynamic search and matching market. Buyers and sellers enter in cohorts over time, meet, and bargain under private information. The optimal centralized mechanism, which involves posting a bid-ask spread, can be decentralized through participation fees charged by the intermediary to both sides. The sum of buyers' and sellers' fees equals the sum of inverse hazard rates of the marginal types, and their ratio equals the ratio of buyers' and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It can be shown that flatfee agency is equivalent to posted prices (i.e., the wholesale model) in our setup. Suppose, for example, that, like in Niedermayer and Shneyerov (2014), the intermediary charges upfront participation fees τ B from buyers and τ S from sellers and then allows buyers and sellers to randomly match and bargain by a random proposer game in which the seller makes an offer with probability α and the buyer with probability 1 − α. In equilibrium, any seller that makes an offer offers p B ; any buyer that proposes offers p S ; and only buyers with v ≥ p B and sellers with c ≤ p S enter.…”
Section: Policy Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be shown that flatfee agency is equivalent to posted prices (i.e., the wholesale model) in our setup. Suppose, for example, that, like in Niedermayer and Shneyerov (2014), the intermediary charges upfront participation fees τ B from buyers and τ S from sellers and then allows buyers and sellers to randomly match and bargain by a random proposer game in which the seller makes an offer with probability α and the buyer with probability 1 − α. In equilibrium, any seller that makes an offer offers p B ; any buyer that proposes offers p S ; and only buyers with v ≥ p B and sellers with c ≤ p S enter.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Starting with the pioneering work by Caillaud andJullien (2001, 2003), Rochet andTirole (2003, 2006), Anderson and Coate (2005) and Armstrong (2006), this literature has primarily focused on monopoly platforms or competition between platforms, abstracting from the exact mechanisms the platforms employ to generate surplus, from traders' options to circumvent the platform, and the platform's incentives to prevent them from so doing. 7 Two notable exceptions that explicitly analyze the platform's trading mechanism are Gomes (2014) and Niedermayer and Shneyerov (2014). Competition between wholesale intermediaries and alternative exchanges fares prominently in the works of Rubinstein and Wolinsky (1987), Stahl (1988), Gehrig (1993), Spulber (1996), Bloch and Ryder (2000), Rust and Hall (2003), Loertscher (2007) and Neeman and Vulkan (2010), which, however, do not address intermediaries' incentives and options to drive out the competing exchanges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 For instance, auctions of incentive contracts, which amount to a left-truncation of the winner's efficiency's probability distribution, deliver for the winner the same power of incentive scheme as if the winner were a monopolist; optimal auctions thus only reduce the fixed component of rewards (Laffont and Tirole (1987)). Another application of this property of the hazard rate is Niedermayer and Shneyerov (2014), in which a platform matches buyers and sellers. The mechanism that maximizes platform profit can, as usual, be derived by maximizing total virtual surplus.…”
Section: Introductionmentioning
confidence: 99%